CHH islands: de novo DNA methylation in near-gene chromatin regulation in maize - Gent, Jonathan I.; Ellis, Nathanael A.; Guo, Lin; Harkess, Alex E.; Yao, Yingyin; Zhang, Xiaoyu; Dawe, R. Kelly (Genome Research, 2013)
Small RNA-mediated regulation of chromatin structure is an important means of suppressing unwanted genetic activity in diverse plants, fungi, and animals. In plants specifically, 24-nt siRNAs direct de novo methylation to repetitive DNA, both foreign and endogenous, in a process known as RNA-directed DNA methylation (RdDM). Many components of the de novo methylation machinery have been identified recently, including multiple RNA polymerases, but specific genetic features that trigger methylation remain poorly understood. By applying whole-genome bisulfite sequencing to maize, we found that transposons close to cellular genes (particularly within 1 kb of either a gene start or end) are strongly associated with de novo methylation, as evidenced both by 24-nt siRNAs and by methylation specifically in the CHH sequence context. In addition, we found that the major classes of transposons exhibited a gradient of CHH methylation determined by proximity to genes. Our results further indicate that intergenic chromatin in maize exists in two major forms that are distinguished based on proximity to genes—one form marked by dense CG and CHG methylation and lack of transcription, and one marked by CHH methylation and activity of multiple forms of RNA polymerase. The existence of the latter, which we call CHH islands, may have implications for how cellular gene expression could be coordinated with immediately adjacent transposon repression in a large genome with a complex organization of genes interspersed in a landscape of transposons.
10.1101/gr.146985.112